2016
DOI: 10.1371/journal.pbio.1002544
|View full text |Cite
|
Sign up to set email alerts
|

Action Enhances Acoustic Cues for 3-D Target Localization by Echolocating Bats

Abstract: Under natural conditions, animals encounter a barrage of sensory information from which they must select and interpret biologically relevant signals. Active sensing can facilitate this process by engaging motor systems in the sampling of sensory information. The echolocating bat serves as an excellent model to investigate the coupling between action and sensing because it adaptively controls both the acoustic signals used to probe the environment and movements to receive echoes at the auditory periphery. We re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 46 publications
0
54
0
1
Order By: Relevance
“…This could explain why responses from frontal neurons are less reliable than those of cortical neurons when tested with simple stimuli such as the pure tones used in this study. The reliability of neuronal responses could increase during active behaviour (i.e., echolocation), which involves a set of variables such as attention, and the build‐up of expectations based on previous sensory history (Feng & Ratnam, ; Wohlgemuth, Kothari, & Moss, ). The roles of these variables are much diminished in experiments conducted in anaesthetized, passively listening animals (this study).…”
Section: Discussionmentioning
confidence: 99%
“…This could explain why responses from frontal neurons are less reliable than those of cortical neurons when tested with simple stimuli such as the pure tones used in this study. The reliability of neuronal responses could increase during active behaviour (i.e., echolocation), which involves a set of variables such as attention, and the build‐up of expectations based on previous sensory history (Feng & Ratnam, ; Wohlgemuth, Kothari, & Moss, ). The roles of these variables are much diminished in experiments conducted in anaesthetized, passively listening animals (this study).…”
Section: Discussionmentioning
confidence: 99%
“…Different behavioral adjustments can change the sensory world that bats are facing or perceiving. During call emission, the animals can variably adjust their sonar beam49 and the echo perception can be influenced through motor behaviors of the head or the pinnae4950. A recent study on insect-eating bats demonstrated that, while hunting, the bats shift their sonar beam and flight path towards the second prey before capturing the immediate prey which increases the capture rate51.…”
Section: Discussionmentioning
confidence: 99%
“…The reliability of neuronal responses could increase during active behavior (i.e. echolocation), which involves a set of variables such as attention, and the build-up of expectations based on previous sensory history (Feng & Ratnam, 2000; Wohlgemuth et al , 2016). The roles of these variables is much diminished in experiments conducted in anesthetized, passively listening animals (this study).…”
Section: Discussionmentioning
confidence: 99%